Analysis on Factors Related with Treatment Behavior of Pulmonary Tuberculosis Patient - Ratnasari, Nita Yunianti; Nurtanti, Susana (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
The total number of pulmonary tuberculosis cases found in Wonogiri district up to Trimester III in 2017 was 602 new cases. Adherence to patient treatment is one of the decisive factors in the success of therapy, but adherence to treatment by pulmonary TB patients is often low. This study aims to evaluate the compliance of treatment of pulmonary tuberculosis patients in Selogiri District Health Center Wonogiri regency. The design of this study used cross-sectional descriptive analysis with data collector in the form of questionnaire as primary data and patient treatment card (Form TB 01) as secondary data. Population of all pulmonary TB patients treated at Selogiri Public Health Center, registered from January 2016 to December 2017. Sampling by total sampling technique. Result of research from 23 total respondents during treatment showed that the number of respondents who adhere to TB treatment was smaller than the non-compliant respondent, that is 10 respondents (43,47%) obedient while respondent did not obey 13 (56,52%). The conclusion of this study there is no relationship between sociodemographic factors, knowledge, drug side effects, history of other diseases, availability of transportation and the role of families and officers with compliance to treatment of pulmonary tuberculosis patients in Selogiri Health Center. This study shows the high rate of non-adherence treatment of lung TB patients.